Complete Genome Sequence of Bacillus subtilis subsp. subtilis Strain 3NA - Reuß, Daniel R. (Genome Announc, 2015)
Bacillus subtilis 3NA reaches high cell densities during fed-batch fermentation and is an interesting target for further optimization as a production strain. Here, we announce the full genome of B. subtilis 3NA. The presence of specific Bacillus subtilis 168 and W23 genetic features suggests that 3NA is a hybrid of these strains.